Expanding Soil Invertebrate Knowledge in Panama: The Genus Lepidocyrtus (Collembola, Entomobryidae) in the Parque Natural Metropolitano as a Study Case - Alba Enguídanos García; Carles Galià-Camps; Claudia Massiel Pérez-González; Dionora Víquez; Eduardo Mateos (Insects)
Panama, located in the heart of the Mesoamerican hotspot, harbors an extraordinary species diversity across the Tree of Life. The Collembola species of the genus Lepidocyrtus play an important role in soil biological processes such as decomposition, being used to monitor soil health and functional parameters. However, the limitation of morphological characters and molecular resources hampers the evaluation of local soil diversity. Here, using 30 Lepidocyrtus specimens collected in the Parque Natural Metropolitano (PNM), we unravel the diversity of this Panamanian protected area through molecular tools and new taxonomic traits. Our phylogenies, in combination with species delimitation analyses, indicate that the PNM harbors an extremely rich community of Lepidocyrtus species, two of them cited in Panama for the first time, and three of them potentially new to science. We highlight that the presence of the dental tubercle and pseudopores on the BP4 region are not monophyletic and, therefore, can be used as supplementary characters to morphologically resolve species complexes. Overall, this study sheds light on the Lepidocyrtus richness of the PNM, which acts as a shelter for Panamanian and the Mesoamerican hotspot species.